1995
DOI: 10.1016/0014-5793(95)00044-a
|View full text |Cite
|
Sign up to set email alerts
|

The use of mass spectrometry to examine the formation and hydrolysis of the phosphorylated form of phosphoglycerate mutase

Abstract: The results are discussed in terms of the kinetic properties of the enzymes. Mass spectrometry would appear to be a powerful method to study the formation and breakdown of phosphorylated proteins, processes which are of widespread significance in regulatory mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…4d). These hydrogen bonds also contribute to the stabilisation of the phosphorylated-histidine group captured in the crystal, which, otherwise, is generally unstable in the aqueous solution with a half-life around 30 minutes 20 .…”
Section: Resultsmentioning
confidence: 99%
“…4d). These hydrogen bonds also contribute to the stabilisation of the phosphorylated-histidine group captured in the crystal, which, otherwise, is generally unstable in the aqueous solution with a half-life around 30 minutes 20 .…”
Section: Resultsmentioning
confidence: 99%
“…The resulting model has 0.28 occupancy phosphohistidine and 0.72 occupancy histidine plus three water molecules. We had no reason to expect histidine phosphorylation prior to crystallization, because the half-life of the phosphohistidine is expected to be of the order of 35 min, as observed with the S. cerevisiae enzyme (25).…”
Section: Methodsmentioning
confidence: 99%
“…For ScPGM to be catalytically competent His8 must be phosphorylated, which requires trace amounts of the cofactor 2,3-bisphosphoglycerate (2,3-BPG) to be present in vivo (Nairn et al, 1995). Site-directed mutagenesis has shown that replacing either of the active-site histidines (His8 and His181) with alanine dramatically reduces ScPGM isomerase activity by preventing the formation of the phosphohistidine moiety (White & Fothergill-Gilmore, 1992).…”
Section: Introductionmentioning
confidence: 99%